FENOMENA HUJAN DALAM INTEGRASI PENDIDIKAN AGAMA ISLAM DAN SAINS - Yusuf, Muhammad; Sa'diyah, Novi Nur (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Islamic education in Indonesia still faces the issue of dichotomy between religious knowledge and secular sciences. This separation stems from historical and epistemological views that position the two as distinct entities. In fact, the integration of religion and science was once a hallmark of Islamic civilization during its golden age, producing renowned scholars who significantly contributed to global progress. This study explores the concept of integrating Islamic Religious Education (IRE) and science, examining it from philosophical, material, and methodological aspects, along with its instructional models. The phenomenon of rain is presented as a case study to demonstrate the harmony between scientific explanations and the Qur’anic descriptions of natural processes. The findings show that integrating IRE and science enhances students' holistic understanding, strengthens their faith, and develops critical thinking skills. Therefore, it is essential to develop an integrated curriculum, provide teacher training, and create learning resources that combine both perspectives to achieve a comprehensive education aligned with national educational goals.